Emerging green spaces in North of Dhaka: suitability analysis in a dense urban settlement - Rehnuma, Manifa; Mohd Yusof, Mohd Johari; Abu Bakar, Shamsul (Faculty of Design & Architecture, Universiti Putra Malaysia, 2017)
Dhaka, the capital of Bangladesh, is acute of green spaces. The uncontrolled urban sprawl is encroaching the lands in the city. The Southern part of Dhaka, the oldest part, offers few large urban green spaces for cultural activity, recreation etc. But there is serious deficiency of neighbourhood and regional urban green open or public gathering space in Northern Dhaka, except the diplomatic zone. Hence, this paper aims to identify the potential lands that can be converted into urban green space by using spatial suitability analysis and GIS. Two aspects have been chosen for desired environmental quality: existing criteria and green indices. The suitability factors are as such: size, accessibility, buffer, Historic-cultural value, existing land use, density, flooding, and water body. These suitability factors are classified into four sets- high, moderate, low and no suitability. The findings assist to synthesize the appropriate land to be adapted as public open space in North of Dhaka. Ultimately, it will help to form a base for generating a greener city in the future.